Comparing the mosque tour program (MTP) between selected mosques - Fatah Yasin, Mohammad Dhiya’ul Hafidh; Fatah Yasin, Muhammad Muthi’ul Haqq; Nik Abdullah, Nik Md. Saiful Azizi (RSIS International, 2025)
Mosque tour program promotes tolerance and understanding through interfaith dialogue. This study examines how mosque tour program in Tuanku Mizan Zainal Abidin Mosque (TMZAM) in Malaysia, Al Fateh Grand Mosque in Bahrain, and Suleymaniye Mosque in Turkiye are conducted through interview and compare the nuances of mosque tour guiding practices across these cultural contexts. This study reveals that the guides in each mosque deliver the information of the purpose of mosque in Islam, and what the Muslims do within. Each mosque also has its own perks. For instance, the location of TMZAM in front of the Palace of Justice, simple but rich decorations of Al Fateh Grand Mosque, and historical and architectural aesthetic in Suleymaniye Mosque. Each mosque has its own selection and training criteria of the volunteers, as well as how they provide supports. This study concludes that the systematic and holistic mosque tour program is essential in achieving the appreciation and understanding of Islam and Muslim culture among non-Muslims. Future researches are suggested to observe the impact of tour program in yet to be studies mosques, as well as producing new tailor-made modules for mosque tour program and interfaith dialogue especially by combining the applicability of others’ module and the uniqueness of the concerned mosques themselves. The inclusion of mosque tour program in national level program such as Visit Qatar or community level like Visit My Mosque also deserve certain attention.